Post exercise tensional curve made with doppler sistem. - Castro Suárez, Danilo; Balboa, Oscar; Tchekmedyian, Vartan; Pittamiglio, Horacio; Matteucci, Pablo; González Ardao, Gino Girardi; Figueredo, Miguel (Cirugía del Uruguay, 1983)
A prospective analisys of 80 studies with ultrasound, in patients with arteriopaty and in a testing group, is performed. Post exercise tensional curves, made with Doppler System and preoperatory arteriography, are compared. With these curves it is able to confirm with a more than 80º/o of accuracy arterial diseases extension, and leve! and if we account with distal vascular· bed for artery repair.